Utmost limits of various solid electrolytes in all-solid-state lithium batteries: A critical review. (July 2019) - Wu, Zhijun; Xie, Zhengkun; Yoshida, Akihiro; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Guan, Guoqing
Abstract: All-solid-state lithium batteries (ASSLBs) with solid electrolytes have attracted great attention for the replacement of traditional lithium batteries with liquid electrolytes due to their advantages such as high safety, excellent electrochemical cycling property and long-term stability. To date, various solid electrolytes including oxide, sulfide and polymer and organic-inorganic hybrid electrolytes have been developed for ASSLBs. Especially, the strategies to improve electrochemical performance especially ionic conductivity and stability of solid electrolytes have been widely studied. However, nowadays, ASSLBs are still not commercialized and used in our daily life. In this article, the situations of the solid electrolytes are critically reviewed, the main challenges and future prospective for the development of solid electrolytes are given and the utmost limits of those state-of-the-art solid electrolytes are analyzed. In addition, the electrode/electrolyte interface modification techniques to make ASSLBs achieving the excellent performance are evaluated. It is expected to provide a guidance for the development of novel solid electrolytes with higher ionic conductivity and environmental stability for ASSLBs. Highlights: State-of-the-art the solid electrolytes are critically reviewed. Main solid electrolytes including oxide, sulfide and polymer electrolytes are introduced. Strategies to improve ionic conductivity and stability of solid electrolytes are supposed. Main challenges and prospects for the development of novel solid electrolytes are given. The utmost limits of various solid electrolytes are analyzed.